Bridging the Gap Between Imagined and Plausible Futures for Refugees: What Students Wish Their Teachers Knew - Vidur Chopra; Sarah Dryden-Peterson; Joumana Talhouk; Carmen Geha (SAGE Publishing, 2024)
There is a gap between the futures that refugee young people imagine will be possible through their education and the plausible futures in exile, where opportunities are truncated by social, economic, and political exclusions. Our study examines how education can narrow this gap. Through interviews with Syrian students in Lebanon, we document fixed and malleable elements of education that refugee students identify as bridging their current education and their futures. Students experience the structures and content of schooling in Lebanon as both exclusionary and immutable, yet their teachers use what we call relational pedagogies rooted in predictability, explaining, fairness, and care to support students' learning and navigation toward future opportunities. While our research focuses on refugees, it has conceptual implications for educators and school systems in other settings where teachers support their marginalized students to make sense of disconnects between what they imagine is possible through school and their future opportunities.